The Effect Analysis of Emotional Intelligence and Work Environment on Employee Performance with Organizational Commitment as Intervening Variables in PT Berkat Bima Sentana - Edward, Yusuf Ronny; Purba, Kuras (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of emotional intelligence and work environment on employee performance through organizational commitment at PT. Berkat Bima Sentana. This research was conducted at PT. Berkat Bima Sentana which lasts for 6 (six) months, starting from August 2019 to January 2020. This study uses a quantitative associative method with structural equation modeling (SEM) analysis tools. The sampling technique used is proportional stratified random sampling using the Slovin formula. The respondents of this study were employees at PT. Berkat Bima Sentana as many as 98 people. The instrument used was a questionnaire to collect data on variables of emotional intelligence, work environment, organizational commitment and employee performance variables. Descriptive analysis results for the variables of emotional intelligence, work environment, organizational commitment and employee performance at PT. Berkat Bima Sentana, it is in the good category. Based on SEM analysis, emotional intelligence and work environment have a positive and significant impact on employee performance through organizational commitment at PT. Berkat Bima Sentana. Contributions from the variables of emotional intelligence, work environment and organizational commitment explain variable employee performance by 0.818 or 81.8%. The remaining 0.182 or 18.2% is influenced by other independent variables not examined in this study.